SOSIALISASI KESETARAAN GENDER PADA PEGAWAI KANTOR KESEJAHTERAAN SOSIAL DAN PEMBERDAYAAN MASYARAKAT KABUPATEN BEKASI - Suryani, Elvira (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
The research is based on the Presidential Instruction No. 9 of 2000 about Gender Mainstreaming that obliges all elements to conduct gender equality in social environment, including in Bekasi, more precise regarding social welfare and empowerment of the Bekasi people. The theories used are from Berger and Luckman named primary and secondary socialization. To analyze this case, the researcher used qualitative research method with indepth interview and purposive sampling